In- vivo diuretic and antiulcer activity in fruits of Buchanania lanzan - Chandra Kishore Tyagi,; Atul Tripathi,; Gyanendra Singh,; Amol Chandekar,; Sunil Sahu, (International Journal of Phytomedicine, 2017)
Ethnopharmacological relevance: The fruits of Buchanania lanzan are used traditionally in the treatment of skin afflictions, sores, ulcers, inflammation and as diuretic (1,21,35,42). The aim of the study was to investigate the antiulcer and diuretic activity of the crude ethanolic and pet. ether extract from the fruits of Buchanania lanzan. Materials and methods: The antiulcer activity of the crude extracts was evaluated in ethanol and pylorus ligation induced model for gastric lesions in Wister albino rats (2,8,12,19). Parameters such as gastric volume, pH and acidity were determined in the pylorus ligation model. Furthermore the diuretic activity was evaluated in comparison of Standard drug i.e. Furosemide. Results: The acute toxicity studies revealed that LD50> 2000mg/kg for the extract. The extract caused a significant (p<0.05) dose-dependent inhibition of ulcer in the ethanol and pylorus ligation induced ulcer models at the dose of 250mg/kg, respectively. And the diuretic activity of extract also found significant (p<0.01) dose dependent increase in urine volume. Both ethanol and aqueous extracts have showed a significant dose-dependent increase in the excretion of electrolytes when compared to the control group. Conclusion: Our data provide a rational base for the folkloric use of Buchanania lanzan in the treatment of ulcers and as diuretic.